Banking reform in Georgia - Metin Mercan (IBSU Scientific Journal (IBSUSJ), 2006)
Georgia's banking system restructure began in 1991 when Soviet Union collopsed.This paper tries to compare and constract the performance of banks and banking system between 1999 and 2004 with banks in other transition countries. Although Georgia banking system showed a long processing in banking sector, it is still lags behind other transition countries Central and Eastern Europe. Neverthless.An efficient financial institution and performance will not come without further economic development and reform of regulation and increase in people's confidence in the financial system as a whole.
Keywords: 330; Transition economies; Banking; Financial reform